2021
DOI: 10.1136/bmjopen-2020-038326
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific prevalence and associated factors of hypertension among elderly Bangladeshi people: findings from a nationally representative cross-sectional survey

Abstract: ObjectiveWe aimed to estimate the gender-specific prevalence and associated factors of hypertension among elderly people in Bangladesh.Design and methodWe analysed data from the food security and nutrition surveillance round 2018–2019. The multistage cluster sampling method was used to select the study population. Hypertension was defined as systolic blood pressure ≥140 mm Hg and/or diastolic blood pressure ≥90 mm Hg and/or having a history of hypertension. We carried out the descriptive analysis, bivariate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
3
17
1
Order By: Relevance
“…20 The study revealed the prevalence of hypertension higher among males compared to female which matched out with the findings from a study conducted in Uttarakhand, India 21 that may be due higher treatment rates among women and males involvement in risky behavior. But contradicted with results from the studies conducted in India 1,13,19,22 and study conducted in low-and middle-income countries. 23 This study showed higher prevalence of hypertension among literate respondents than illiterate.…”
Section: Discussionmentioning
confidence: 59%
“…20 The study revealed the prevalence of hypertension higher among males compared to female which matched out with the findings from a study conducted in Uttarakhand, India 21 that may be due higher treatment rates among women and males involvement in risky behavior. But contradicted with results from the studies conducted in India 1,13,19,22 and study conducted in low-and middle-income countries. 23 This study showed higher prevalence of hypertension among literate respondents than illiterate.…”
Section: Discussionmentioning
confidence: 59%
“…This finding is similar to a cross-sectional rural study in Bangladesh that found that about 18.8% of Bangladeshi males were hypertensive [ 31 ]. Contrarily, the prevalence of hypertension among females reported is relatively lower than the 56.2% reported by Hanif [ 13 ]. Also, the overall prevalence of obesity (BMI) was 23.2%; 27.1% females and 18.8% males.…”
Section: Discussionmentioning
confidence: 80%
“…About 12 million (18%) of Bangladeshi adults aged 25 and above are hypertensive [ 3 ]. More females (56.2%) than males (43.8%) are hypertensive [ 13 ] and poorly manage high blood pressure (BP) [ 14 ]. Shifts in nutrition increase overnutrition in Bangladesh [ 15 ] as the excessive intake of dietary macro- and micronutrients, overnutrition, alters body fat composition [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further details on sample size calculation, cluster selection and participant enrolment were published elsewhere. 25 Figure 1 demonstrates the process of selecting the study participants for this analysis. Data collection and quality control A structured questionnaire, developed in English, and translated to Bengali, was used.…”
Section: Sample Size and Sampling Techniquesmentioning
confidence: 99%
“…More details on data collection and anthropometric measurements have been described elsewhere. 25 Outcome variable IPA was estimated following the 2010 WHO guidelines on PA. According to the guideline, persons aged 18-64 years, and ≥65 years, are required to perform at least 150 min of moderate intensity, or 75 min of vigorous intensity or an equivalent combination of PA in a week.…”
Section: Sample Size and Sampling Techniquesmentioning
confidence: 99%